International Monetary Fund Annual Report 2009 : Fighting the Global Crisis. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2009)
The IMF's 2009 Annual Report chronicles the response of the Fund's Executive Board and staff to the global financial crisis and other events during financial year 2009, which covers the period from May 1, 2008, through April 30, 2009. The print version of the Report is available in eight languages (Arabic, Chinese, English, French, German, Japanese, Russian, and Spanish), along with a CD-ROM (available in English only) that includes the Report text and ancillary materials, including the Fund's Financial Statements for FY2009.